Magnetic chitosan functionalized with β‐cyclodextrin as ultrasound‐assisted extraction adsorbents for the removal of methyl orange in wastewater coupled with high‐performance liquid chromatography. Issue 17 (31st July 2018) - Dai, Yunliang; Row, Kyung Ho
Abstract: Three types of choline chloride based deep eutectic solvents were prepared and used to modify magnetic chitosan. The adsorption capacity of the three deep‐eutectic‐solvent‐modified magnetic chitosan/carboxymethyl‐β‐cyclodextrin for removing methyl orange from wastewater was examined. The different deep eutectic solvents were used to strengthen the adsorption capacity of magnetic chitosan. Deep‐eutectic‐solvent‐modified magnetic chitosan/carboxymethyl‐β‐cyclodextrin materials were characterized by Fourier transform infrared spectroscopy and Brunauer–Emmett–Teller surface area measurements. Among the three deep eutectic solvents, choline chloride/glycerol (1:2) modified magnetic chitosan/carboxymethyl‐β‐cyclodextrin showed the highest adsorption capacity to methyl orange. Therefore, choline chloride/glycerol (1:3, 1:4, 1:5, 1:6) deep eutectic solvents were prepared for the assay, and choline chloride/glycerol‐modified magnetic chitosan/carboxymethyl‐β‐cyclodextrin prepared with choline chloride/glycerol (1:3) (volume: 40 μg, contact time: 30 min, and pH: 6) had the best adsorption capacity over the concentration range of 10–200 μg/mL.